Will Multi-Parametric Magnetic Resonance Imaging be the Future Tool to Detect Clinically Significant Prostate Cancer? - Giannarini, Gianluca; Zazzara, Michele; Rossanese, Marta; Palumbo, Vito; Pancot, Martina; Como, Giuseppe; Abbinante, Maria; Ficarra, Vincenzo (Frontiers in Oncology, 2014)
Multiparametric magnetic resonance imaging is an emerging imaging modality for diagnosis, staging, characterization and treatment planning of prostate cancer. In this report we reviewed the literature for studies assessing the accuracy of multiparametric magnetic resonance imaging in detecting clinically significant prostate cancer, and we critically examined the future role of this imaging tool in various clinical diagnostic settings. There is accumulating evidence suggesting a high accuracy of multiparametric magnetic resonance imaging in ruling out clinically significant disease. Although definition for clinically significant disease widely varies, the negative predictive value is very high at up to 98%. Multiparametric magnetic resonance imaging should, thus, further be evaluated for application in different clinical scenarios in which it is desirable to reduce the proportion of unnecessary prostate biopsies and to limit the detection of indolent disease, such as opportunistic screening, persistent prostate cancer suspicion in men with previous negative prostate biopsies, and eligibility for active surveillance. Continued improvement in standardization of technical parameters, functional sequences and image reporting systems is a pre-requisite for a rapid and successful dissemination of this imaging modality.